Pengembangan dan Implementasi Kurikulum Ismuba Sekolah Muhammadiyah di Sukabumi - Triwidyastuti, Triwidyastuti; Aziz, Muhammad Thariq; Noor, Iqbal (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This service aims to provide understanding and understanding of the ISMUBA curriculum, develop and implement it in Muhammadiyah schools in Sukabumi City and Regency. Methodology/approach: The method for implementing this service includes three stages: (1) preparation through observation and interviews to identify needs, determine targets, and prepare proposals; (2) implementation in the form of workshops, training in preparing RPPs, and implementation of the ISMUBA curriculum; and (3) evaluation and follow-up planning. Results/findings: The results are: (1) Muhammadiyah schools understand, develop and implement the ISMUBA curriculum; (2) ISMUBA teachers' teaching skills increase; (3) ISMUBA character education is implemented; (4) ISMUBA learning uses appropriate lesson plans; (5) Starting to create teaching materials for ISMUBA subjects; (6) SMP MBS Al-Kaarimah becomes a pilot project school that provides information to other schools regarding the implementation of the ISMUBA curriculum; (7) Teachers begin to understand the ISMUBA curriculum; and (8) Most Muhammadiyah schools have developed and implemented the ISMUBA curriculum well. Conclutions: The workshop and training produced products in the form of lesson plans, teaching materials and learning media. It is hoped that this service will be the first step for Muhammadiyah Sukabumi School to be able to implement the Ismuba curriculum correctly. Limitations: The main limitation of this service is that the regional coverage only includes Sukabumi and surrounding area, so the implementation and impact of the program has not yet spread to other areas. As a result, the potential for utilizing the ISMUBA curriculum cannot be felt evenly in other region Contribution: The main limitation of this service is that its coverage area only covers Sukabumi and its surroundings.